Exploring factors influencing Contrimetric adoption and word-of-mouth advocacy in academic libraries - Yu, Lifeng (Malaysian Journal of Library and Information Science, 2025)
Contrimetric is an AI-powered bibliometric plugin designed to provide real-time citation tracking, personalised content recommendations, reference validation, and dynamic research impact dashboards. This study investigates the factors influencing the adoption of Contrimetric, an emerging AI-powered bibliometric tool, in academic libraries across China. Drawing on the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), the research examines how perceived ease of use, perceived usefulness, social influence, and facilitating conditions affect behavioural intention, which in turn drives word-of-mouth (WOM) advocacy among academic peers. Data were collected through a structured survey administered to librarians and researchers in Chinese universities, yielding 400 valid responses representing diverse academic disciplines and institutional settings. The results confirm that perceived ease of use, perceived usefulness, social influence, and facilitating conditions all have significant positive effects on behavioural intention, and behavioural intention positively influences WOM. Mediation analysis further indicates that behavioural intention mediates the relationships between perceived usefulness, social influence, facilitating conditions, and WOM, while the indirect path for perceived ease of use is marginally significant at the 10% level. These findings highlight the critical role of institutional support and peer influence in fostering advocacy, such as recommending Contrimetric to colleagues and encouraging its adoption in academic environments. The study contributes to the technology adoption literature by extending TAM and UTAUT beyond initial adoption, incorporating post-adoption WOM behaviours as a critical outcome, and offers practical implications for policymakers and library administrators seeking to enhance research visibility through AI-enabled services.